Divergence in Photoperiod Responses of a Classical Biological Control Agent, Galerucella calmariensis (Coleoptera: Chrysomelidae), Across a Climatic and Latitudinal Gradient. Issue 2 (21st December 2020) - Wepprich, Tyson; Grevstad, Fritzi S
Abstract: A key knowledge gap in classical biological control is to what extent insect agents evolve to novel environments. The introduction of biological control agents to new photoperiod regimes and climates may disrupt the coordination of diapause timing that evolved to the growing season length in the native range. We tested whether populations of Galerucella calmariensis L. have evolved in response to the potential mismatch of their diapause timing since their intentional introduction to the United States from Germany in the 1990s. Populations collected from 39.4° to 48.8° latitude in the western United States were reared in growth chambers to isolate the effects of photoperiod on diapause induction and development time. For all populations, shorter day lengths increased the proportion of beetles that entered diapause instead of reproducing. The critical photoperiods, or the day length at which half of a population diapauses, differed significantly among the sampled populations, generally decreasing at lower latitudes. The latitudinal trend reflects changes in growing season length, which determines the number of generations possible, and in local day lengths, at the time when beetles are sensitive to this cue. Development times were similar across populations, with one exception, and did not vary with photoperiod. These results show that there was sufficient genetic variation from the two German source populations to evolve different photoperiod responses across a range of environmental conditions. This study adds to the examples of rapid evolution of seasonal adaptations in introduced insects.